2008
DOI: 10.1016/j.amjcard.2007.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Noninvasive Estimate of Pulmonary Vascular Resistance to Predict Mortality, Heart Failure, and Adverse Cardiovascular Events in Patients With Stable Coronary Artery Disease (from the Heart and Soul Study)

Abstract: Pulmonary vascular resistance (PVR) is an important hemodynamic variable that affects prognosis and therapy in a wide range of cardiovascular and pulmonary conditions. We sought to determine whether a noninvasive estimate of PVR predicts adverse outcomes in patients with stable coronary artery disease. Using Doppler echocardiography we measured the estimated PVR (defined as the ratio of the tricuspid regurgitant velocity [TRV] to the velocity-time integral [VTI] of the right ventricular outflow tract [RVOT])… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 10 publications
(10 reference statements)
0
25
0
1
Order By: Relevance
“…DE has also been shown to provide an estimate of PVR, measured as the ratio of the tricuspid regurgitant velocity (TRV) to the VTI of the right ventricular outflow tract (RVOT). TRV/VTI RVOT has been shown to predict mortality and adverse cardiovascular events in patients with stable coronary artery disease (25). However, because the relation of TRV/VTI RVOT to PVR has been established in a population with an average PVR of 2 mm Hg/L/min, its application in patients with very high PVR values (i.e., pulmonary vascular disease) remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…DE has also been shown to provide an estimate of PVR, measured as the ratio of the tricuspid regurgitant velocity (TRV) to the VTI of the right ventricular outflow tract (RVOT). TRV/VTI RVOT has been shown to predict mortality and adverse cardiovascular events in patients with stable coronary artery disease (25). However, because the relation of TRV/VTI RVOT to PVR has been established in a population with an average PVR of 2 mm Hg/L/min, its application in patients with very high PVR values (i.e., pulmonary vascular disease) remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…A TRV of 2.5 m/sec or greater is also associated with a high risk of death in other conditions, such as congestive heart failure. 25 This association between increased TRV and mortality in SCD is significant, and has been confirmed in multiple studies, 20,21,[26][27][28] although it remains to be determined whether this measurement and, its association with mortality, reflects true pulmonary hypertension per se, or is a biomarker of disease severity and systemic vasculopathy in SCD. Right heart catheterization studies suggested that 6-11% of adults with SCD have pulmonary hypertension defined by a mean pulmonary artery pressure greater than or equal to 25 mmHg.…”
Section: Pulmonary Hypertension In Adults With Sickle Cell Diseasementioning
confidence: 94%
“…A RVP pode ser estimada pela simples relação do pico da IT (em metros por segundo) pela integral da velocidade pelo tempo do fluxo na VSVD (em centímetros). [87][88][89] Esta relação não é confiável em RVP muito elevadas, com valores > 8 Wood, conforme calculada por métodos hemodinâmicos invasivos.90 Um dos métodos para determinar a RVP está ilustrado na Figura 14.…”
Section: Resistência Vascular Pulmonarunclassified